Evaluation of DNA damage and Antioxidant Status with G6PD-deficient in Iraqi Patients - Saud, Asmaa (Iraqi Journal of Science, 2025)
Thirty blood samples of clinically glucose-6-phosphate dehydrogenase (G6PD)-deficient patients were collected from pediatrics hospital and Al- Kadhumia teaching hospital in Baghdad, Iraq. .Besides that, blood samples were taken from 30 apparently healthy individuals (without Hemoglobinopathy disorders ( as a control group. The apoptotic response shown by G6PD-deficient patients was evaluated using neutral method of Comet assay. Comet assay result was demonstrated as comet index which represent a mean of the scored that calculate from the ratio of cell diameters (L/W) of total cells in each sample. These results revealed that lymphocytes exhibited an increase apoptosis percentage (44.5%) compare with percentage of control (7%). This revealed that there was DNA damage in G6PD-deficient patients. On the other hand, repeated blood transfusion in G6PD-deficient patients may lead to oxidative tissue injury by secondary iron overload. The results indicated that there was a significant decrease in catalase activity levels (P<0.05), whereas the lipid peroxidation end product (MDA) levels and both G-Px, SOD activity levels were significantly increased in all G6PD-deficient patients (P < 0.05) as compared with the control group. MDA values showed a significant positive correlation with G-Px levels (r = + 0.756), while it was observed negative correlated with catalase levels (r = - 0.352). These data indicates an increase in free radical generation and thus antioxidant defense mechanisms is impaired in peroxidation associated with a significant elevation in MDA levels in the erythrocytes of the G6PD deficiency than that found in the control group which demonstrate the presence of an increased oxidative stress due to reduction in NADPH which is generated in erythrocytes. This suggests that oxidative stress and reduced antioxidant defense mechanism play an important role in pathogenesis and DNA damage of G6PD-deficient patients.